An Amino‐Acid‐Based Self‐Healing Hydrogel: Modulation of the Self‐Healing Properties by Incorporating Carbon‐Based Nanomaterials. Issue 44 (13th September 2013) - Roy, Subhasish; Baral, Abhishek; Banerjee, Arindam
Abstract An amino‐acid‐based (11‐(4‐(pyrene‐1‐yl)butanamido)undecanoic acid) self‐repairing hydrogel is reported. The native hydrogel, as well as hybrid hydrogels, have been thoroughly characterized by using various microscopic techniques, including transmission electron microscopy (TEM), atomic force microscopy (AFM), Raman spectroscopy, fluorescence spectroscopy, FTIR spectroscopy, X‐ray diffraction, and by using rheological experiments. The native hydrogel exhibited interesting fluorescence properties, as well as a self‐healing property. Interestingly, the self‐healing, thixotropy, and stiffness of the native hydrogel can be successfully modulated by incorporating carbon‐based nanomaterials, including graphene, pristine single‐walled carbon nanotubes (Pr‐SWCNTs), and both graphene and Pr‐SWCNTs, within the native gel system. The self‐recovery time of the gel was shortened by the inclusion of reduced graphene oxide (RGO), Pr‐SWCNTs, or both RGO and Pr‐SWCNTs. Moreover, hybrid gels that contained RGO and/or Pr‐SWCNTs exhibited interesting semiconducting behavior.